2011
DOI: 10.1002/jmv.22223
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of human papillomaviruses in fresh frozen breast cancer samples

Abstract: While the etiology of breast cancer remains enigmatic, some recent reports have examined the role of human papillomavirus (HPV) in breast carcinogenesis. The purpose of this study was to determine the prevalence of HPV in breast cancer tissue using PCR analysis and sequencing. Fifty-four (54) fresh frozen breast cancers samples that were removed from a cohort of breast cancer patients were analyzed. Samples were tested for HPV using comprehensive PCR primers, and in situ hybridization was performed on paraffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 31 publications
(47 reference statements)
3
52
1
2
Order By: Relevance
“…En este estudio, la presencia de VPH fue detectada en el 63.6% de las muestras de cáncer de mama, mientras que solo el 4.5% de las biopsias de tejido con patología benigna fueron positivas para este virus. Esta frecuencia de detección se encuentra dentro del rango publicado previamente en todo el mundo, con una prevalencia que oscila entre el 10 y el 86% 30 , en 2011, detectaron mediante PCR múltiple y PCR consenso un 61.06 y un 50% de casos positivos para ADN de VPH, respectivamente.…”
Section: Discussionunclassified
“…En este estudio, la presencia de VPH fue detectada en el 63.6% de las muestras de cáncer de mama, mientras que solo el 4.5% de las biopsias de tejido con patología benigna fueron positivas para este virus. Esta frecuencia de detección se encuentra dentro del rango publicado previamente en todo el mundo, con una prevalencia que oscila entre el 10 y el 86% 30 , en 2011, detectaron mediante PCR múltiple y PCR consenso un 61.06 y un 50% de casos positivos para ADN de VPH, respectivamente.…”
Section: Discussionunclassified
“…[105][106][107][108][109] Nevertheless the role of HPV in breast carcinogenesis is by far not certain and further randomized control trials are required to establish the definite role of HPV in breast cancer development.…”
Section: Breast Cancermentioning
confidence: 99%
“…Ala-eddin Al Moustafa, 1,2,3, * Amber Yasmeen, 1 Lina Ghabreau 4 and Nizar Akil group. 6 Herein, we report that high-risk HPVs type 45, 51, 52 and 58 are frequently present in colorectal cancer in this population (p < 0.001, p < 0.001, p < 0.001 and p < 0.0001, respectively) ( Table 1), in some cases multiple types of HPV infections were detected.…”
Section: Does the Syrian Population Have To Wait For The New Generatimentioning
confidence: 99%
“…1 Persistent infection with high-risk HPVs is necessary for the development of premalignant lesions and/or progression of the disease. 1 Furthermore, high-risk HPVs have carcinogenic effects at several other anatomical sites in women and men such as colorectal, head and neck (HN) as well as breast, [2][3][4] studies showed that high-risk HPVs are present in roughly 91%, 30% and 50% of these cancers, respectively. 3,4 Therefore, 9%, 70% and 50% of these cancer are negative for high-risk HPVs; however, we believe that some of these highrisk HPVs-negative cases could be infected by low-risk HPVs.…”
mentioning
confidence: 99%